2021
DOI: 10.1017/s0007114521000908
|View full text |Cite
|
Sign up to set email alerts
|

The effect of supplemental bioactive fatty acids on growth performance and immune function of milk-fed Holstein dairy calves during heat stress

Abstract: This study aimed to evaluate the effects of different supplemental fat sources [soybean oil (SBO) as a source of n-6 fatty acid and fish oil (FO) as a source of n-3 fatty acids] in the starter feed of milk-fed dairy calves during the hot season. Forty Holstein calves (3 d of age; 39.67 kg of body weight; ten calves per group) were randomly assigned to the experimental treatments as follows: (1) starter feed supplemented with no fat source (CON), (2) starter feed supplemented with 3% SBO (DM basis), (3) starter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 55 publications
(133 reference statements)
2
8
1
Order By: Relevance
“…This can be lead to providing higher amino acid available to be absorbed in small intestine which is supportive for growing calves (Kazemi‐Bonchenari et al, 2018). Regarding the supplemental FA, no changes were found for ruminal pH or ruminal activity which may be mostly related to its ruminal protection which is in line with previous works on preruminant animals (Kandi et al, 2020; Mohtashami et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This can be lead to providing higher amino acid available to be absorbed in small intestine which is supportive for growing calves (Kazemi‐Bonchenari et al, 2018). Regarding the supplemental FA, no changes were found for ruminal pH or ruminal activity which may be mostly related to its ruminal protection which is in line with previous works on preruminant animals (Kandi et al, 2020; Mohtashami et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…Although some previous literatures verified anti-inflammatory effect of n-3 FA supplementation in dairy calves (Ballou & DePeters, 2008;Karcher et al, 2014;Mohtashami et al, 2021), our study also detected an interaction of n-3 FA source with grain source. Our results showed that LO supplementation that is rich in n-3 FA can be strategy to offset or at least reduce the inflammatory impact of BG feeding in dairy calves.…”
Section: Blood Metabolites and Inflammatory Markerscontrasting
confidence: 85%
See 1 more Smart Citation
“…Additionally, ω-3 PUFA can also increase the production of some anti-inflammatory cytokines [ 153 , 154 ]. Studies in cattle and sheep have shown that dietary supplementation of ω-3 PUFA can improve growth performance even in animals that are under little or no acute stress [ 155 , 156 , 157 , 158 ]. Thus, it is not surprising that daily supplementation of ω-3 PUFA-rich fish oil to heat-stressed feedlot lambs mitigated the rise in circulating granulocytes, granulocyte:lymphocyte ratios, body temperatures, and respiratory rates, which in turn improved muscle growth and rescued intramuscular fat content [ 159 , 160 ].…”
Section: The Role Of Inflammation In Heat Stressmentioning
confidence: 99%
“…Thus, it is not surprising that daily supplementation of ω-3 PUFA-rich fish oil to heat-stressed feedlot lambs mitigated the rise in circulating granulocytes, granulocyte:lymphocyte ratios, body temperatures, and respiratory rates, which in turn improved muscle growth and rescued intramuscular fat content [ 159 , 160 ]. In heat-stressed dairy calves, fish oil reduced circulating TNFα and other inflammatory indicators, which was associated with reduced body temperatures and respiratory rates as well as improved feed efficiency [ 158 ]. Although fish oil is an effective and relatively inexpensive option for targeting inflammation, it should be noted that its taste and smell can create an aversion for some animals and can even result in reduced feed intake [ 161 ].…”
Section: The Role Of Inflammation In Heat Stressmentioning
confidence: 99%